The effect of travel distance on health-related quality of life for patients with nephrolithiasis - Narang, Gopal L. (Can Urol Assoc J, 2020)
INTRODUCTION: Urolithiasis causes a significant impact on health-related quality of life (HRQOL). Patients with kidney stones have high levels of stress and anxiety. Symptom resolution often requires treatment. Travel distance is a barrier to care but little is known about its effects on HRQOL. We hypothesize that increased distance to treatment site is associated with decreased HRQOL. METHODS: Patients with a history of stones were enrolled at 11 tertiary centers as part of the QOL Stone Consortium of North America. HRQOL data were obtained using the Wisconsin Stone Quality of Life questionnaire (WISQOL). We calculated distance between patient and treatment site using national ZIP codes. We used linear models to evaluate the effect of distance on HRQOL, while also considering demographics data, stones/symptom status, and distance. RESULTS: Of the 1676 enrolled patients, 52% were male, 86% non-Latino White, and the mean age was 53 years. Mean distance to treatment site was 63.3 km (range 0–3774), with 74% reporting current stones and 45% current symptoms. WISQOL score and distance were negatively correlated for patients reporting current stones and symptoms (p=0.0010). Linear modelling revealed decreased WISQOL scores for patients with symptoms as distance increased from treatment site (p=0.0001), with a 4.7-point decrease for every 100 km traveled. CONCLUSIONS: Stone disease imposes significant burden on patients’ HRQOL due to a variety of factors. Patients with active stone symptoms report worse HRQOL with increased distance to their treatment site. Possible etiologies include travel burden, increased disease burden, decreased healthcare use, and delays in care.